A Darwinian Pilgrim's Late Progress. (10th December 2018) - Ruse, Michael
Abstract : This is the final part of an autobiographical series which retraces the most significant events, collaborations, and research results of Michael Ruse's 55-year-long career in the history and philosophy of science. In this installment, Ruse's increasing engagement with historiography leads him to rethink and tackle the role of values in science. The intertwined topics summarized here are considered as they developed between the 1990s and the 2010s: the mediation between empiricism and social constructivism; the historical study of the idea of qualitative, biological "progress" in evolutionary biology as drawn from coeval social ideas; the paradox according to which "progress" is formally eschewed and yet implicitly present in modern evolutionary biology; the development of evolutionary biology from pseudoscience tied to social progress to popular science to full-fledged professional science; Darwinism as hopeful, progressive "religion" contrasted with progress-less Darwinian theory; meaning in a Darwinian world, and the development of a Darwinian existentialism.